Innovation in islamic education evaluation through kahoot application based on artificial intelligence - Triana Hermawati; Nur Fadilah Tanjung; Khabib Muhammad Fauzan; Fiska Ilyasir (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The purpose of this article is to examine the model of integrating Artificial Intelligence (AI) in the evaluation of Islamic Religious Education (PAI), particularly through the use of the Kahoot application. In today’s digital era, AI opens up innovative opportunities to create a more interactive, real-time, and engaging evaluation process for students. This article explores how the integration of AI into quiz-based platforms such as Kahoot can enhance the effectiveness of PAI learning assessments, deepen students' understanding of Islamic material, and encourage active participation in the learning process. The research method used is a literature review, which involves analyzing various relevant academic sources. The findings indicate that the use of AI in Kahoot-based evaluations not only facilitates teachers in monitoring learning achievements accurately and efficiently but also fosters an adaptive, collaborative, and data-driven learning environment. This digital-based evaluation allows students to learn according to their individual abilities and interests, while teachers benefit from instant feedback to develop more targeted teaching strategies.